Protective Effects of Maclurin against Benzo[a]pyrene via Aryl Hydrocarbon Receptor and Nuclear Factor Erythroid 2-Related Factor 2 Targeting - Jangsoon Kim; See-Hyoung Park; Seyoung Yang; Sae Woong Oh; Kitae Kwon; Se Jung Park; Eunbi Yu; Hyeyoun Kim; Jung Yoen Park; Seoyoung Choi; Seoyeon Yang; Minkyung Song; et al. (Antioxidants, 2021)
Benzo[a]pyrene (B[a]P), a polycyclic aromatic hydrocarbon formed during the incomplete combustion of organic matter, has harmful effects. Therefore, much research is ongoing to develop agents that can mitigate the effects of B[a]P. The aim of this study was to examine the effect of maclurin, one component of the branches of Morus alba L., on the B[a]P-induced effects in HaCaT cells, a human keratinocyte cell line. Maclurin treatment inhibited aryl hydrocarbon receptor (AHR) signaling as evidenced by reduced xenobiotic response element (XRE) reporter activity, decreased expression of cytochrome P450 1A1 (CYP1A1), and reduced nuclear translocation of AHR. The B[a]P-induced dissociation of AHR from AHR-interacting protein (AIP) was suppressed by maclurin. Maclurin also inhibited the production of intracellular reactive oxygen species (ROS) induced by B[a]P. In addition, the antioxidant property of maclurin itself was demonstrated by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. Furthermore, maclurin activated antioxidant response element (ARE) signaling through enhancement of ARE luciferase reporter activity and the expression of ARE-dependent genes including nuclear factor (erythroid-derived 2)-like 2 (Nrf2) and heme oxygenase-1 (HO-1). Nrf2 activation and its nuclear translocation were promoted by maclurin through p38 MAPK activation. These data indicate that maclurin had antagonistic activity against B[a]P effects through activation of Nrf2-mediated signaling and inhibition of AHR signaling and, suggesting its potential in protecting from harmful B[a]P-containing pollutants.